Slides to Philosophy 167: Class 3 -- Kepler's Astronomia Nova: The Orbit of Mars -- Part 4. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Generally corresponds to the video segment: Class 3, Part 4.